Perilaku Maladministrasi Dalam Pelayanan Publik Pasca Reformasi Birokrasi di Kota Pekanbaru, Provinsi Riau Indonesia - Wahyudi, Rodi (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
Bureaucratic reform program has not been able to change the behavior of bureaucraticmaladministration in Indonesia. Although there has been a change in the structure of government andpublic administration system and the implementation of bureaucratic reform program since 2006, butstill disappointing quality of public services community. The question is why the behavior ofmaladministration bureaucracy still exists in the public service in Indonesia ?. The study wasconducted to examine the behavior of maladministration difference before and after the reform of thebureaucracy. Two research methods used in this study. Questionnaires were completed by 250 civilservants. The second method is depth interviews with nine key informants. Five agencies that provideservices has been selected as the study site. The study found that the level of bureaucraticmaladministration of public servants to work after the reform era higher than civil servants employedprior to the reform era. This means that the agency Ombudsman of the Republic of Indonesia, civilservice law and a code of ethics for civil servants still unable to discipline the behavior ofmaladministration reduce bureaucracy. Governments need to develop a special program to change thebad behavior of civil servants in the ministry through the cultivation of moral values based on religiousteachings.